1972
DOI: 10.1001/archpedi.1972.02110090115018
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Tear Gas on an Infant Following Prolonged Exposure

Abstract: A 4-month-old male infant developed pneumonitis following a prolonged exposure to tear gas (CS or orthochlorobenzylidene malononitrile). The patient had a persistent leukocytosis (white blood cell count 20,000 to 30,000/cu mm) with predominance of lymphocytes on peripheral blood smear and had a slow resolution of the pneumonitis radiologically. A discussion of the toxicity of the two most widely used tear gases\p=m-\chlo-roacetophenone (CN) and CS\p=m-\onthe respiratory system indicates that both agents are ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Sublethal exposures to moderately high concentrations of CS or CN may produce localised inflammation in the bronchopulmonary mucosa which resolves, but in some instances may act as a focus for the development of a secondary respiratory infection. Such a human case has been described for a prolonged non-lethal exposure to CS by Park and Giammona (1972), and highlights the necessity for clinical observation and investigation of anyone exposed to very high concentrations of irritant smoke, particularly if prolonged.…”
Section: Discussionmentioning
confidence: 89%
“…Sublethal exposures to moderately high concentrations of CS or CN may produce localised inflammation in the bronchopulmonary mucosa which resolves, but in some instances may act as a focus for the development of a secondary respiratory infection. Such a human case has been described for a prolonged non-lethal exposure to CS by Park and Giammona (1972), and highlights the necessity for clinical observation and investigation of anyone exposed to very high concentrations of irritant smoke, particularly if prolonged.…”
Section: Discussionmentioning
confidence: 89%
“…Studies on volunteers indicate that exposure to about 0.5 to 1 mg/m 3 CS for 90 minutes in an exposure chamber produced symptoms of tightness in the chest and in some cases difficulty in breathing was experienced, particularly upon initial exposure [8]. Subjects were able to tolerate exposure at these levels throughout the 90 minutes' duration of this experiment.…”
Section: Correlation Between Forced Vital Capacity (Fvc) and Forced Ementioning
confidence: 80%
“…In [12] tested the ability for human to work in a CS contaminated environment for duration of two weeks, whereby it is found that test subject accuracy decreases due to symptoms of respiratory failure. In [8] reported the case of a previously there is a negative relationship between the variables studies. It is found that FVC reading collected in this research will decreases as the duration of exposure to CS increases.…”
Section: Correlation Between Forced Vital Capacity (Fvc) and Forced Ementioning
confidence: 97%
“…Regarding adverse effects on reproductive function and pregnancy, the Himsworth Committee 404 concluded that CS exposure had not significantly affected reproductive physiology; however, meaningful epidemiological studies were not conducted to address more fully the issue of reproductive risks. The potential adverse effects in the very young following exposure to CS was addressed also by Park and Giammona, 407 who have described the effects of CS in a 4-month-old infant after prolonged exposure. The infant manifested severe respiratory distress and symptoms included copious nasal and oral secretions, sneezing and coughing and obstruction of the upper airways.…”
Section: Chlorobenzylidene Malononitrile (Cs)mentioning
confidence: 97%